The new pteridophyte classification and sequence employed in the Herbarium Bogoriense (BO) for Malesian ferns. - Wita Wardani; Arief Hidayat; Dedy Darnaedi (Research Center for Biology, 2012)
BO followed sequences written in the first Flora Malesiana series II for Malesian fern specimen arrangement and flora listing, which thenÂ updated as revision for pteridophyte families done successively.Â However, the sequence in this incomplete flora to some extent is problematic. Recent advancement in pteridophyte classification is available and expected to stabilize delimitation of families and genera. The paper reviews the two sequences and presents a consensus for specimen arrangement and flora listing of Malesian fern.